SEXUAL HARASSMENT AT WORKPLACE ACT, 2013: A REVIEW - Mahapatra, Sneha; Roy, Koyel; Kaur, Yugdeep; Sharma, Sunny; Banerjee, Debosmita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The “Prevention of Sexual Harassment” (POSH) of “Women at Workplace Act” was introduced in India in 2013 to address the issue of sexual harassment (SH) against women in the workplace. The act requires all employers to establish internal complaint committees (ICCs) to investigate complaints of SH and to take appropriate action against the perpetrator. This abstract highlight the role of the POSH Act in creating a safer and more conducive work environment for women. The act has helped in empowering women by providing them with a platform to voice their grievances, ensuring that they are heard and taken seriously. It has also increased awareness about SH and its impact on women’s mental and physical health, career prospects, and overall well-being. The POSH Act has contributed to creating a positive work environment where women feel more comfortable and confident in their roles. However, there are still many challenges to be addressed, such as the implementation of the law in smaller organizations, ensuring the confidentiality of the complainant, and creating awareness about the act among all employees. Overall, the POSH Act has been a crucial step in making the workplace better for women and in promoting gender equality and respect in the workplace.